A new strategy of endosymbiont midgut bacteria in ant (Ponerinae) - Caetano, Flávio Henrique [UNESP]; Zara, Fernando Jose [UNESP]; Bution, M. L. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The location and ultrastructure of bacteria associated with microvilli in the midgut of Odontomachus bauri were examined by transmission electron microscopy. These filamentous type bacteria are the second morphotype described in the midgut of this ant. They colonizes only the ectoperitrophic space, more specifically attaching along microvilli. A thick capsule attaches bacteria to microvilli and protect them from acidic pH and digestive enzymes. Details of the location and association with microvilli are discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bacteria; Microvilli; Ants; Ponerinae